Book Review. Issue 1 (1st June 2018) - Gray, Sally
Experimental Fashion: Performance Art, Carnival and the Grotesque Body, Francesca Granata (2016)London: I. B. Tauris, 256 pp., ISBN: 9781784533786, h/bk, £59.00/$115.00